Disordered Intestinal Microbial Communities During Clostridioides difficile Colonization and Subsequent Infection of Hepatic Cirrhosis Patients in a Tertiary Care Hospital in China - Chen, Yunbo; Lv, Tao; Yan, Dong; Zheng, Lisi; Zheng, Beiwen; Wang, Jingxia; Gu, Silan; Li, Lanjuan (Frontiers in Cellular and Infection Microbiology, 2022)
Patients with hepatic cirrhosis are more susceptible to Clostridioides difficile infection (CDI) and colonization with Clostridioides difficile (C. difficile). Asymptomatic C. difficile colonization is thought to predispose to subsequent CDI. However, the dynamic gut microbiota changes remain unclear. In this study, we used 16S rRNA gene sequencing to longitudinally monitor alterations in the intestinal microbiota of 22 hepatic cirrhosis patients with toxigenic C. difficile colonization at admission (pre-CDI) and developed CDI during hospitalization, subdivided into pre-CDI and CDI. 21 hospitalized cirrhotic patients without C. difficile colonization served as controls (HC). Compared with HC, pre-CDI and CDI samples had significantly decreased microbial richness and diversity, a significantly higher relative abundance of opportunistic pathogen Enterococcus, and a lower relative abundance of beneficial symbionts, such as Faecalibacterium, Dorea, and Roseburia. Three biomarkers showed high accuracy for distinguishing pre-CDI samples from HC with an area under the curve (AUC) up to 0.81. In conclusion, our study explored the changes of the gut microbiome before and after CDI. The gut microbial richness as well as diversity in CDI patients were notably reduced, relative to controls. Imbalance of the intestinal flora may be related to the risk for development of CDI. Identifying key members of the gut microbiota and illustrating their roles and mechanisms of action in CDI development are important avenues for future research.